1989
DOI: 10.1111/j.1558-5646.1989.tb02617.x
|View full text |Cite
|
Sign up to set email alerts
|

FEMALE CHOICE AND SEXUAL SELECTION OF MALE WING MELANIN PATTERN INPIERIS OCCIDENTALIS(LEPIDOPTERA)

Abstract: Abstract. -Using field experiments, I examined the role of 13 melanin-pattern elements in mate choice by female Pieris occidentalis butterflies, Males that mated successfully differed significantly from unsuccessful males in the extent of marginal forewing melanization but not on the basis of the entire forewing pattern, Deletion of the marginal forewing melanin characters significantly reduced the mating success of manipulated males relative to controls under field conditions, Female choice in P, occidentalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 61 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…The 1991 study also indicated selection for increased melanin on the margins of the dorsal forewings (fm2). This is of interest because previous studies show that melanin in this wing region is correlated positively with mating success in male P. occidentalis in Colorado and at Corfu (Wiernasz 1989;Kingsolver unpubl. data).…”
Section: Selection and Polyphenism In Wing Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1991 study also indicated selection for increased melanin on the margins of the dorsal forewings (fm2). This is of interest because previous studies show that melanin in this wing region is correlated positively with mating success in male P. occidentalis in Colorado and at Corfu (Wiernasz 1989;Kingsolver unpubl. data).…”
Section: Selection and Polyphenism In Wing Traitsmentioning
confidence: 99%
“…Thus, we predict that hotter thermal environments will selectively favor lower values of hb and pv, and higher values of ds and ft4 (or correlated traits; see below), compared with cooler environments. Studies with P. occidentalis in Colorado show that aspects of melanin pattern are also important in female choice of male mates (Wiernasz 1989). Experimental manipulations of pattern demonstrate that males with less melanin on the marginal and transverse bands of the DFW have a lower acceptance rate as mates by females (Wiernasz 1989).…”
Section: Analyzing Melanin Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been considered an accelerator for heat gain (e.g. Kettlewell, 1973;Kingsolver and Wiernasz, 1991;Clusella-Trullas et al, 2007;Reguera et al, 2014); however, it also is associated with UV radiation protection (Gunn, 1998;Callaghan et al, 2004;Calbó et al, 2005;Reguera et al, 2014), crypsis (Kettlewell, 1973;Endler, 1984;Reguera et al, 2014) and intra-specific communication or sexual selection (Wiernasz, 1989;Fedorka et al, 2013). Additionally, the advantages of melanism may be associated with local conditions (local adaptation; Castella et al, 2013), as a result of phenotypic plasticity (Alho et al, 2010) or the interaction between predator avoidance and thermoregulation (Lindstedt et al, 2009).…”
Section: D O N O S O B a R R O S I L J O S E I L M A R T O R mentioning
confidence: 99%
“…Melanins are a ubiquitous class of pigments present in a large variety of taxa (Hill 1992). Levels of pigmentation have been assumed to be adaptive through processes as diverse as camouflage (Kettlewell 1976), sexual display (Wiernasz 1989;Senar 1999), thermoregulation (Watt 1968), disease resistance (Barnes andSiva-Jothy 2000, Wilson et al 2001), photoprotection (Ortonne 2002), and strengthening of plant cells and insect cuticles (Riley 1997).…”
mentioning
confidence: 99%